Energy-saving method for technogenic waste processing - Dikhanbaev, Bayandy; Gomes, Chandima; Dikhanbaev, Aristan Bayandievich (Public Library of Science, 2017)
Dumps of a mining-metallurgical complex of post-Soviet Republics have accumulated a huge amount of technogenic waste products. Out of them, Kazakhstan alone has preserved about 20 billion tons. In the field of technogenic waste treatment, there is still no technical solution that leads it to be a profitable process. Recent global trends prompted scientists to focus on developing energy-saving and a highly efficient melting unit that can significantly reduce specific fuel consumption. This paper reports, the development of a new technological method—smelt layer of inversion phase. The introducing method is characterized by a combination of ideal stirring and ideal displacement regimes. Using the method of affine modelling, recalculation of pilot plant’s test results on industrial sample has been obtained. Experiments show that in comparison with bubbling and boiling layers of smelt, the degree of zinc recovery increases in the layer of inversion phase. That indicates the reduction of the possibility of new formation of zinc silicates and ferrites from recombined molecules of ZnO, SiO2, and Fe2O3. Calculations show that in industrial samples of the pilot plant, the consumption of natural gas has reduced approximately by two times in comparison with fuming-furnace. The specific fuel consumption has reduced by approximately four times in comparison with Waelz-kiln.